ANXIETY DISORDERS IN CORONARY ARTERY DISEASE PATIENTS: NARRATIVE REVIEW - Anna Leśniewska; Patryk Macuk; Oliwia Sójkowska-Sławińska; Michał Gniedziejko; Jakub Roszak; Paulina Bernecka; Bartosz Żegleń; Aleksandra Gradek; Bartosz Michał Skorupski; Julia Tarnowska (International Journal of Innovative Technologies in Social Science, 2025)
Objective: Psychiatric comorbidities, particularly anxiety and depressive disorders, are highly prevalent among patients with cardiovascular disease and represent significant contributors to adverse clinical outcomes and healthcare resource utilization. This investigation examined the association between evidence-based mental health interventions and subsequent healthcare utilization patterns in patients with heart failure (HF) and coronary artery disease.Methods: We evaluated the impact of psychiatric treatment modalities, including pharmacological therapy and psychotherapeutic interventions, on hospital readmission rates and emergency department (ED) utilization among cardiovascular patients with comorbid anxiety or depressive disorders.Key Findings: Mental health treatment demonstrated substantial protective effects against adverse healthcare utilization outcomes. Patients receiving combination therapy (both pharmacotherapy and psychotherapy) exhibited the most pronounced benefit, with a 75% reduction in hospital readmission risk and a 74% decrease in ED visits compared to untreated controls. Monotherapy approaches also yielded significant improvements: psychotherapy alone was associated with a 49% reduction in readmission risk and 53% decrease in ED utilization, while pharmacological intervention alone resulted in 58% and 49% risk reductions for readmissions and ED visits, respectively. These findings remained statistically significant across all treatment modalities examined.Conclusions: The implementation of appropriate mental health interventions, whether through pharmacological management, psychotherapeutic approaches, or combined treatment strategies, represents a critical component in the comprehensive care of cardiovascular patients with psychiatric comorbidities. These data provide compelling evidence that addressing psychological comorbidities is not merely adjunctive but essential for optimizing clinical outcomes, reducing healthcare burden, and improving the overall prognosis of patients with HF and coronary disease. Integration of psychiatric care into standard cardiovascular management protocols should be considered a clinical imperative.